2018
DOI: 10.1001/jamafacial.2018.1163
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Persian Language Version of the Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS)

Abstract: problem (Figure). The curve of SCHNOS-C was shifted toward greater severity of symptoms.Discussion | The SCHNOS demonstrated overall perfect ability to distinguish different levels of perceived nasal symptoms. The SCHNOS-O score was effective at differentiating between patients with and without symptoms, whereas the SCHNOS-C score was most effective when discriminating symptoms at higher severity levels. Although the sample was large, it was limited to one university clinic with predominantly younger and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Nasal Obstruction Symptom Evaluation (NOSE) survey and Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) were utilized to assess patient's nasal obstructive symptoms and nasal cosmesis 17,18 . The SCHNOS survey is a full validated PROM consisting of 10 questions divided into obstructive (SCHNOS‐O) and cosmetic (SCHNOS‐C) domains 19–25 . The SCHNOS‐O was calculated as a sum of the obstruction item scores (numbers 1–4), divided by 20 and multiplied by 100, whereas the SCHNOS‐Cosmesis (SCHNOS‐C) was similarly calculated as a sum of the cosmetic item scores (numbers 5–#10), divided by 30 and multiplied by 100, as previously described 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Nasal Obstruction Symptom Evaluation (NOSE) survey and Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) were utilized to assess patient's nasal obstructive symptoms and nasal cosmesis 17,18 . The SCHNOS survey is a full validated PROM consisting of 10 questions divided into obstructive (SCHNOS‐O) and cosmetic (SCHNOS‐C) domains 19–25 . The SCHNOS‐O was calculated as a sum of the obstruction item scores (numbers 1–4), divided by 20 and multiplied by 100, whereas the SCHNOS‐Cosmesis (SCHNOS‐C) was similarly calculated as a sum of the cosmetic item scores (numbers 5–#10), divided by 30 and multiplied by 100, as previously described 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Among the quality-of-life (QOL) instruments' currently available for both aesthetic and functional rhinoplasty, the SCHNOS, which has been developed with a robust development technique, 3 is more precise, 2 more comprehensive, 4 and has been the most extensively validated. [5][6][7][8][9][10] The SCHNOS-O can be utilized as both a clinical and a screening tool for nasal obstruction, and the SCHNOS-C is a reliable clinical tool for cosmetic outcomes. 5 The twofactor structure of SCHNOS has been verified by confirmatory factor analysis, 6 and also demonstrated that two of the 10 SCHNOS items, item 1 (having a blocked or obstructed nose) and item 9 (how well the nose suits the face can be employed as a quick screening tool for the evaluation of nasal obstruction and assessing cosmetic disadvantage, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…1) was created specifically to aid surgeons in assessing both nasal obstruction symptoms and nasal cosmesis in rhinoplasty patients. Among the quality‐of‐life (QOL) instruments' currently available for both aesthetic and functional rhinoplasty, the SCHNOS, which has been developed with a robust development technique, 3 is more precise, 2 more comprehensive, 4 and has been the most extensively validated 5–10 . The SCHNOS‐O can be utilized as both a clinical and a screening tool for nasal obstruction, and the SCHNOS‐C is a reliable clinical tool for cosmetic outcomes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Its usefulness, being a simple and quickly filled questionnaire, can reflect not only the individual health status but also a tool that can be used to compare outcomes in academic research of rhinoplasty patients. 6,10 A high internal consistency demonstrates the reliability of this tool for EP-SCHNOS-O, EP-SCHNOS-C, and EP-SCHNOS with Cronbach's α values of 0.93, 0.95, and 0.96, respectively (►Table 3). This study also showed a positive and significant correlation between each item of the EP-SCHNOS-O and EP-SCHNOS-C (►Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…12 SCHNOS has been already validated in several languages such as Arabic, French, Turkish, Spanish, and Brazilian Portuguese, lacking a European Portuguese version, as previously discussed. 10,[13][14][15][16] The small number of participants can be a limitation of this study, although several similar translation studies achieved a validation process with a similar number of participants. [13][14][15] Since our results showed the reliability and validity of the European Portuguese SCHNOS, we consider that a more robust association could only be stronger with a greater sample size.…”
Section: Discussionmentioning
confidence: 99%